A clinical evaluation of the soft tissue conditions of betel nut chewers - Bernardo, Jean A.; Leyeza, Ma. Amelita S.; Natividad, Gervasio (Adviser).
The clinical oral condition of 22 betel nut chewers in one barrio were evaluated. Eight chewers out of the total sample revealed oral lesions, with two lesions not directly related to betel nut chewing. The remaining six chewers had the lesions within the vicinity of the mandibular buccal sulcus and the angle of the mouth. Chewing frequency was found to be a major factor in the appearance of the lesions, with quid staying time, length of chewing years, and poor oral hygiene as predisposing factors.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Oral health; Mouth -- Care and hygiene